Bibliometric trends in ophthalmology 1997-2009 - Mansour, Ahmad M. (2015)
Aims: To track citation patterns in ophthalmic journals and contrast them with major medical and surgical journals from 1997 to 2009. In addition, we want to familiarize the ophthalmic community with bibliometrics indices. Materials and Methods: Data retrieved from Institute for Scientific Information and related websites include 2-year journal impact factor JIF, 5-year impact, Eigenfactor score, H-factor, Article Influence score, and SCImago factor. Results: JIF rose steadily around 10% annually in ophthalmic journals, and likewise for major medical and surgical journals. JIF correlated with recent bibliometric indicators like 5-year impact, H index, and SCImago factor but not with Eigenfactor. Ophthalmic journals publishing reviews, basic science, or large volume on broad range of topics ranked at the top for JIF, while subspecialty journals tended to have low JIF. JIF of subspecialty journal Retina rose from 0.740 (rank 23) in 2000 to 3.088 in 2007 (rank 6). Conclusions: JIF tends to rise annually by 10% in medical, surgical, and ophthalmic fields. Journals publishing reviews, basic science, or large volume on broad range of topics rank at the top for JIF. The rapid rise of JIF for Retina unlike other subspecialties that stayed status quo is multifactorial: Change in editorial policies (introduction of review articles and omission of case reports) and technological advances in the retinal field.